2014
DOI: 10.1177/0142331214532002
|View full text |Cite
|
Sign up to set email alerts
|

Improved APF strategies for dual-arm local motion planning

Abstract: Manipulator motion planning is a classic problem in robotics, with a number of complete solutions available for their motion in controlled (industrial) environments. Due to recent technological advances in the field of robotics, there has been a significant development of more complex robots with high fidelity sensors and more computational power. One such example has been a rise in the production of humanoid robots equipped with dual-arm manipulators which require complex motion planning algorithms. Also, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Even though the success of the search depends on the heuristic, the algorithm showed good performance in comparison with several samplingbased planners. Byrne et al [16] proposes a method consisting of goal configuration sampling, subgoal selection and Artificial Potential Fields (APF) motion planning. It was shown that the method improves APF performance for independent and cooperative dual-arm manipulation tasks.…”
Section: Dual-arm Motion Planningmentioning
confidence: 99%
“…Even though the success of the search depends on the heuristic, the algorithm showed good performance in comparison with several samplingbased planners. Byrne et al [16] proposes a method consisting of goal configuration sampling, subgoal selection and Artificial Potential Fields (APF) motion planning. It was shown that the method improves APF performance for independent and cooperative dual-arm manipulation tasks.…”
Section: Dual-arm Motion Planningmentioning
confidence: 99%
“…The motor in each joint provided more torque than the exact value to hold the object (Lee et al, 2014a). Byrne et al (2015) proposed strategies for dual-arm local motion planning in unknown environments. They were based on modified artificial potential fields, which use configuration sampling and sub-goal selection to avoid the local minimum.…”
Section: Introductionmentioning
confidence: 99%
“…For safety, speed and reliability it is imperative that collisions are avoided at all cost. Well established techniques of path planning and collision avoidance include artificial potential fields [5] and graph based search methods, such as rapidly-exploring random trees (RRT) [6]. These methods are effective but do not always compute the most efficient paths and incorporating dynamic constraints can be challenging.…”
Section: Introductionmentioning
confidence: 99%